Minimally invasive surgery versus transcatheter aortic valve replacement: a systematic review and meta-analysis - Ahmed Bendary (BMJ Publishing Group, 2021)
Transcatheter aortic valve replacement (TAVR) has recently been approved for use in patients who are at intermediate and low surgical risk. Moreover, recent years have witnessed a renewed interest in minimally invasive aortic valve replacement (miAVR). The present meta-analysis compared the outcomes of TAVR and miAVR in the management of aortic stenosis (AS). We conducted an electronic search across six databases from 2002 (TAVR inception) to December 2019. Data from relevant studies regarding the clinical and length of hospitalisation outcomes were extracted and analysed using R software. We identified a total of 11 cohort studies, of which seven were matched/propensity matched. Our analysis demonstrated higher rates of midterm mortality (≥1 year) with TAVR (risk ratio (RR): 1.93, 95% CI: 1.16 to 3.22), but no significant differences with respect to 1 month mortality (RR: 1.00, 95% CI: 0.55 to 1.81), stroke (RR: 1.08, 95% CI: 0.40 to 2.87) and bleeding (RR: 1.45, 95% CI: 0.56 to 3.75) rates. Patients undergoing TAVR were more likely to experience paravalvular leakage (RR: 14.89, 95% CI: 6.89 to 32.16), yet less likely to suffer acute kidney injury (RR: 0.38, 95% CI: 0.21 to 0.69) compared with miAVR. The duration of hospitalisation was significantly longer in the miAVR group (mean difference: 1.92 (0.61 to 3.24)). Grading of Recommendations Assessment, Development and Evaluation assessment revealed ≤moderate quality of evidence in all outcomes. TAVR was associated with lower acute kidney injury rate and shorter length of hospitalisation, yet higher risks of midterm mortality and paravalvular leakage. Given the increasing adoption of both techniques, there is an urgent need for head-to-head randomised trials with adequate follow-up periods.